Role of Piriformospora indica and Pseudomonas fluorescens as Growth Promoting Agents in Biotized Micropropagated Plants of Populus deltoides - Gosal, S.K.; Chandi, G.K.; Gosal, S.S.; Varma, A. (Indian Journal of Agroforestry, 2020)
Micropropagated Poplar (Populus deltoides) plantlets were biotized during hardening with a fungus Piriformospora indica and bacteria Pseudomonas fluorescens in single and dual inoculations. Plants were biotized with P. fluorescens by two methods viz. root dipping and soil drenching. The per cent colonization of P. indica as studied microscopically was observed maximum (74.3%) after 60 days of biotization. Maximum population count of P. fluorescens after 30 days of biotization was observed as 0.34 x 106 cfu g-1 root (rhizoplane) and 94 x 106 cfu g-1 soil (rhizosphere) which increased upto 0.58 x 106 cfu g-1 root Â (rhizoplane) and 199 x 106 cfu g-1 soil (rhizosphere) after 60 days. Biotization increased the survival rate of micropropagated plants. Dual biotization using root dipping method exhibited maximum survival (94.5%). Dual biotization (root dipping) showed maximum shoot length (20.30 cm), shoot dry weight (2.15 g), number of lateral rootlets (12.66) and root dry weight (0.44 g) as recorded after 90 days of transplantation in the greenhouse. However, maximum root length was 14.80 cm in case of single biotization using P. fluorescens (root dipping). Dual biotization using root dipping proved to be the best method for increasing the survival rate and growth of micropropagated plants.